Hybrid process of persulfate-based advanced oxidation with MeOₓ-functionalized catalytic ceramic membrane for synergistic removal of micropollutants: recent developments, new insights, and prospects - Liangdy, Arvin (2023)
The hybrid catalytic oxidation and membrane filtration process has attracted increasing research interest for synergistic removal of recalcitrant micropollutants (MPs) in water and wastewater. The use of catalytic ceramic membrane (CCM) in the hybrid process further intensifies the organic pollutants degradation and mineralization. This critical review aims to provide a state-of-the-art review and new perspectives on the sulfate radical (SO4•−)-based hybrid processes with the application of metal oxide (MeOx)-functionalized catalytic ceramic membranes (CCMs). The fabrication methods of MeOx-CCMs developed to immobilize the MeOx catalysts onto/within the ceramic membranes and several advanced characterization techniques (i.e., X-ray absorption spectroscopy, 3D-imaging, and operando characterization techniques) and methods to identify reactive oxygen species (ROS) are summarized. The performances of the hybrid processes are evaluated in terms of process configurations, organics removal mechanisms and mass balance studies. Notably, the importance of both the MeOx-CCMs intrinsic catalytic and membrane properties in intensifying the MPs removal efficiency and water filtration of the hybrid process is highlighted. Meanwhile, the technical challenges in implementation of the hybrid process for real water remediation including poor MPs rejection and potential formation of toxic by-products are identified. Lastly, the application prospects and future research directions of the hybrid process are proposed, namely (i) development of novel, facile and low-cost techniques for fabrication of CCMs, (ii) strategy to develop MeOx-CCMs for nanofiltration, and (iii) incorporation of different heterogeneous catalytic oxidation processes in the hybrid process.